2011
DOI: 10.1007/s00894-011-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative theoretical study of the catalytic activities of Au 2 - and AuAg- dimers for CO oxidation

Abstract: The detailed mechanisms of catalytic CO oxidation over Au(2)(-) and AuAg(-) dimers, which represent the simplest models for monometal Au and bimetallic Au-Ag nanoparticles, have been studied by performing density functional theory calculations. It is found that both Au(2)(-) and AuAg(-) dimers catalyze the reaction according to the similar mono-center Eley-Rideal mechanism. The catalytic reaction is of the multi-channel and multi-step characteristic, which can proceed along four possible pathways via two or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
3
7
0
Order By: Relevance
“…This indicates that O 2 prefers to bind to Ag-site of AuAg À similar to the previous study. 17 This fact was further confirmed by calculated longer O-O distance (1.390 Å) in AuAg À -O 2 than that in AgAu À -O 2 (1.373 Å), which were in close agreement with previously reported values. 17 The amount of electron transfer from the dimer to O 2 in these two complexes was 0.645 e in AuAg À -O 2 and 0.557 e in AgAu À -O 2 .…”
Section: Complexes Of Au-ag à With O 2 and Nosupporting
confidence: 90%
See 3 more Smart Citations
“…This indicates that O 2 prefers to bind to Ag-site of AuAg À similar to the previous study. 17 This fact was further confirmed by calculated longer O-O distance (1.390 Å) in AuAg À -O 2 than that in AgAu À -O 2 (1.373 Å), which were in close agreement with previously reported values. 17 The amount of electron transfer from the dimer to O 2 in these two complexes was 0.645 e in AuAg À -O 2 and 0.557 e in AgAu À -O 2 .…”
Section: Complexes Of Au-ag à With O 2 and Nosupporting
confidence: 90%
“…Previous investigations 17,[29][30][31][32][33] showed that the B3LYP functional was sufficiently accurate for describing noble-metal systems. To further verify the reliability of our methods, we also calculated the bond lengths for Au-Ag À , NO and O 2 and dissociation energy calculations for Au-Ag À and NO to compare the corresponding experimental values.…”
Section: Reliability Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Comparative studies of Au 2 À -and AuAg À -catalyzed CO oxidation found that the strong catalytic activity of AuAg À could be attributed to the synergistic effects of the Au and Ag atoms. 30 Through an investigation of the LH mechanism on Ag-NC, Jiang and co-workers found that 55-atom Ag-NC showed strong catalytic activity toward CO oxidation. 31 Kim et al studied the mechanism of 13-atom Ag-NCs-catalyzed CO oxidation, and showed that structural fluxionality accounted for the catalytic activity of small nanoparticles.…”
Section: Introductionmentioning
confidence: 99%